(untitled) (Rudarsko-geološko-naftni zbornik, 2020)
This paper analyzes the possible role of liquefied natural gas (LNG) in the region in reducing carbon dioxide (CO2) emissions by replacing a certain part of solid fossil fuels. Increasing natural gas consumption, declining North Sea natural gas reserves and increased natural gas production costs in Europe combined have created new opportunities for LNG in Europe. The Energy Strategy of Croatia is focused on intensifying the transit position for natural gas that could establish Croatia as a primary LNG market for countries from the region, which shows that the Energy Strategy supports LNG. Concerning LNG’s introduction into the regional gas market, this paper analyses the possibility of establishing a regional gas hub. The region in this paper includes the following countries: Croatia, Serbia, Bosnia and Herzegovina, Hungary, Slovenia, and North Macedonia. On the other hand, the observed markets are not organized and sufficiently liquid, which is a crucial precondition for hub establishment. In order to decrease the region’s dependence on pipeline natural gas, it is necessary to construct gas interconnections between Croatia – Serbia, Croatia – Bosnia and Herzegovina and Serbia – North Macedonia. With the mentioned interconnections, the region could achieve greater security of natural gas supply. This paper discusses the possibility of utilizing the full capacity of a LNG terminal as a source of natural gas supply for the purpose of replacing solid fossil fuels in the region’s primary energy consumption. By replacing solid fossil fuels with natural gas, it is possible to achieve significant savings on CO2 emissions, which contributes towards a green and sustainable future.